Effect of detergents on the germination and initial growth of habanero pepper (Capsicum chinense Jacq.) plants (2023)
Due to the risk of contamination caused by the use of detergents, there is a growing need to evaluate their effects on plant development. The effects of three household detergents with different phosphorus concentrations (D0P: 0, D1P: 7162 and D2P: 14256 mg kg-1) on the germination and growth of Capsicum chinense Jacq. were evaluated. To study the effects on germination, the seeds were exposed to 0, 50, 500, 1,000 and 2,000 mg L-1 of the three detergents for 20 days. To evaluate the effects on growth, the experiment was performed in hydroponics and seedlings were exposed to 0, 500 and 2,000 mg L-1 of D0P and D2P detergents. The detergents caused no changes in the germination percentage, but they did modify the speed of the germination process, which was dependent on the type and concentration of the detergent. D0P delayed the onset of germination at 2,000 mg L-1 while D1P and D2P accelerated it at 1000 and 2,000 mg L-1. The three detergents stimulated the weight and vigor of the seedlings at 500 mg L-1 and inhibited them at 2,000 mg L-1, with greater inhibitory effects with D0P and D2P. The hydroponics experiment evidenced that the concentration of 500 mg L-1 of D0P and D2P reduced root and leaf growth by about 50% from day 3 of exposure and caused damage to most of the leaf tissue, being toxic to the crop at this stage. The 500 mg L-1 dose enhanced the vigor of the germinated seedlings; however, it proved to be toxic when applied to 10-day-old seedlings in hydroponic conditions.